2001
DOI: 10.1063/1.1389857
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of liquid-crystal alignment and chiral symmetry-breaking

Abstract: We carry out Monte Carlo simulations to investigate the effect of molecular shape on liquid-crystal order. In our approach, each model mesogen consists of several soft spheres bonded rigidly together. The arrangement of the spheres may be straight (to represent uniaxial molecules), Z-shaped (for biaxial molecules), or banana-shaped (for bent-core molecules). Using this approach, we investigate the alignment of the nematic phase by substrates decorated with parallel ridges. We compare results for wide and narro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 25 publications
2
38
1
Order By: Relevance
“…Even for this GB model, the N u phase disappeared for an intermediate 170 degrees apex angle. Interestingly, close to the nematic-smectic phase transition a spontaneous chirality symmetry breaking [136] was reported [133,134,137] to produce organisations related to those predicted by Lubensky and Radzihovsky [4], or observed by Görtz and Goodby [19]. The presence of a central transverse dipole [135] suppresses the N u phase to give transitions from isotropic to smectic phases, and this is at variance with results from atomistic simulations (see later on).…”
Section: Multi-site Modelscontrasting
confidence: 52%
“…Even for this GB model, the N u phase disappeared for an intermediate 170 degrees apex angle. Interestingly, close to the nematic-smectic phase transition a spontaneous chirality symmetry breaking [136] was reported [133,134,137] to produce organisations related to those predicted by Lubensky and Radzihovsky [4], or observed by Görtz and Goodby [19]. The presence of a central transverse dipole [135] suppresses the N u phase to give transitions from isotropic to smectic phases, and this is at variance with results from atomistic simulations (see later on).…”
Section: Multi-site Modelscontrasting
confidence: 52%
“…[3] It has also been predicted by Monte Carlo simulations that steric interaction under influence of repulsive forces alone is sufficient to explain the induction of mesoscopic chirality. [4] Nevertheless, molecular simulations of mesoscopic ensembles based on the structure of the single molecule are computationally very intensive and require either a limit on the number of molecules or greatly simplified molecular shapes. [4] A promising approach for gaining insight into the process of intermolecular chirality transfer is the investigation of the self-assembly of chiral molecules on solid surfaces, where the chirality transfer is limited to two dimensions.…”
mentioning
confidence: 99%
“…In the works by Memmer 9 and Johnston et al 10,11 , isotropic, nematic, tilted smectic, and helical phases were found, depending on the molecular bend angle 9,10 and the magnitude of the dipole moment 11 . Xu et al studied composite molecules made up of repulsive soft spheres, and found isotropic and tilted crystalline phases 12 . More recently, we have studied composite molecules made up of Lennard-Jones spheres -so called 'composite LennardJones molecules' (CLJMs) -which exhibit isotropic, nematic, tilted smectic, and tilted crystalline phases 13 .…”
Section: Introductionmentioning
confidence: 99%